Coordenação pedagógica no ensino fundamental: atribuições e práticas na escola de ensino fundamental no município de Acará - NONATO, Valdilene Maria Vasconcelos (2019)
The present research has as its theme: Pedagogical Coordination in Elementary School: Attributions and practices at the Elementary School in the city of Acará, which aims to know the attributions and practices that the Pedagogical Coordinator has in the school and how the relationships and coordinator mediations with teachers at school. It aims to reflect on the role of the Pedagogical Coordinator, to know his role in educational practice, to seek to understand the various attributions that fit them as the professional who promotes articulation, mediation and transformation in the school environment. The approach used was qualitative; the type of research chosen was the Case Study, through data collection carried out at the EMEIF Manoel Antônio de Castro, in the city of Acará. Observation, interviews and document analysis. The Pedagogical Coordinator needs to be a professional capable of continuing education with teachers, seeking to contribute to an education able to meet the needs of students, hence the relevance of knowing the identity of the Pedagogical Coordinator, to perform a quality work providing subsidies. For school and especially for teachers. Given the questions and reflections raised through the studies and interviews, the following result was obtained: The Pedagogical Coordinator presents himself as an important professional in the teaching-learning process and in the continuing education of teachers, being a mediator and articulator of pedagogical actions. Always aiming at improving education.